FRI0036 Population pharmacokinetics (pk) of anakinra in subjects with rheumatoid arthritis (ra). (1st June 2001) - Yang, B; Frazier, J; McCabe, D; Young, JD
Abstract : Background: Anakinra is a recombinant interleukin-1 receptor antagonist that reduces signs and symptoms and slows joint destruction in RA patients in clinical trials. Population PK analysis was conducted on data from RA patients treated with anakinra. Objectives: The objective was to investigate the effect of covariates such as creatinine clearance (CLcr), body weight (WT), age, and sex, on anakinra PK. Methods: Subjects (n = 341) received daily SC injections of anakinra at 30, 75, or 150 mg for 6 months; one plasma sample for anakinra measurement was collected from each subject at baseline, and at weeks 1, 4, 12, 20, and 24 before anakinra administration for that day. Plasma samples were analysed for anakinra levels by an ELISA method. Plasma anakinra data were analysed by nonlinear mixed-effects modelling using NONMEM. "Population" mean PK parameters, intersubject variability in the PK parameters, and residual error were estimated. Results: Anakinra PK appeared to be dose independent and was adequately described by a one-compartment model with first-order absorption and elimination. Results showed that anakinra volume of distribution (Vd/F) increased linearly with increasing WT (Vd/F = 0.142 * WT, p < 0.05). Both CLcr and WT were significant predictors of anakinra plasma clearance (CL/F); clearance increased with increasing CLcr and WT (CL/F = 23.0 + 0.343 * CLcr + 0.713 * WT, p < 0.05). The plasma clearance of anakinra was higher in men (164 ± 25 mL/min, n = 79) than in women (144 ± 22 mL/min, n = 262) and higher in younger subjects (< 65 yr, 152 ± 24 mL/min, n = 262) than in older subjects (> 65 yr, 138 ± 23 mL/min, n = 79), these differences could be explained by differences in CLcr and WT. Conclusion: Results from population PK analyses confirmed nonclincial and clinical data, which showed the kidney to be a major clearance organ for anakinra.